Perspective Boarding Education Renewal K.H. Abdul Wahid Hasyim and Its Relevance to Contemporary Islamic Education - Sabar Sabar; Sulthan Syahril; Syaripudin Basyar (Edumaspul: Jurnal Pendidikan, 2024)
The development of Islamic boarding school education has brought changes to various aspects of human life. Although traditionalists are often not completely affected, there are similarities between traditional Islamic boarding school educational institutions and modernist changes. One of the Islamic boarding school education figures who made a contribution was KH. Abdul Wahid Hasyim, is known as a bridge between Islamic boarding school civilization and modern civilization. This research focuses on two main problems, namely the form of reform of Islamic boarding school education from the perspective of KH. Abdul Wahid Hasyim and its relevance to contemporary Islamic education. The research method used is library study, collecting data from various library sources such as books and articles related to Islamic boarding school education reform. The research results show that the idea of renewing Islamic boarding school education by KH. Abdul Wahid Hasyim emerged from disappointment with colonialism which was detrimental to indigenous people. These reform efforts include institutional, methodological, library and curriculum aspects. KH. Abdul Wahid Hasyim also founded Madrasah Nizamiyyah and developed Islamic higher education, which later developed into the State Islamic University (UIN). This reform plays an important role in advancing Islamic boarding school education and educating society. Its relevance to contemporary Islamic education can be seen in the transformation of Islamic higher education institutions in Indonesia. Thus, the contribution of KH. Abdul Wahid Hasyim has formed the foundation for the development of modern Islamic education in this country.